2016
DOI: 10.1162/ling_a_00215
|View full text |Cite
|
Sign up to set email alerts
|

The Unity of Focus: Evidence from Sign Language (ASL and LSF)

Abstract: In spoken languages, focus (i) is normally realized by phonological prominence, which in English is effected by higher pitch, greater loudness and longer duration (e.g. Katz and Selkirk 2011). Semantically, it (ii) signals the activation of alternatives (e.g. Rooth 1996), and (iii) it has diverse effects, ranging from contrastive (as in (1)a) to exhaustive (as in (1)b). 1(1) a. I'll introduce John to Mary, and then I'll introduce BILL to her.b. If you invite John OR Mary, the party will be a success. => no inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Almost all SLs studied to date have shown that body leans are the most common strategy employed by SLs for the expression of contrast between two referents. In ASL, forward and backward body leans are consistently used for expressing contrastive relations (Wilbur & Patschke 1998, Schlenker et al 2016. In NGT left and right body leans are used in order to express contrast (Van der Kooij et al 2006, Kimmelman 2014.…”
Section: Contrast In Sign Languagesmentioning
confidence: 99%
“…Almost all SLs studied to date have shown that body leans are the most common strategy employed by SLs for the expression of contrast between two referents. In ASL, forward and backward body leans are consistently used for expressing contrastive relations (Wilbur & Patschke 1998, Schlenker et al 2016. In NGT left and right body leans are used in order to express contrast (Van der Kooij et al 2006, Kimmelman 2014.…”
Section: Contrast In Sign Languagesmentioning
confidence: 99%
“…Rooth 1996). Schlenker et al (2016) discuss ASL and LSF instances of Brow Raise marking exhaustive focus (which can be analyzed in terms of a covert only), but also contrastive focus. Wilbur's analysis might have to be slightly extended to capture the latter cases.…”
Section: Brow Raisementioning
confidence: 99%
“…For reader-friendliness, we follow Schlenker et al (2016) in using a revised transcription system (the SLASH-notation 7 ) in which sign modulations are indicated by modifying the glosses themselves, while non-manuals appear above the capitalized glosses, with a line indicating their duration, and iconic symbols whenever possible -in the order: 1. body changes 2. head changes 3. facial expressions, e.g. /}^.…”
Section: Transcription Conventionsmentioning
confidence: 99%
See 2 more Smart Citations